Characteristics of purple sweet potato yoghurt based on the use of different carbon sources: Karakteristik Yoghurt Ubi Jalar Ungu Berdasarkan Penggunaan Sumber Karbon yang Berbeda - Iswanty, Trian; Sholahuddin, Sholahuddin; Hartanti, Lucky (Universitas Slamet Riyadi Surakarta, 2025)
Purple sweet potato yogurt is a form of local food innovation made from milk fermented by lactic acid bacteria (LAB), with the addition of purple sweet potato paste to enhance flavor and color, thereby increasing consumer appeal. During fermentation, LAB require carbon derived from carbohydrates as an energy source for their metabolism and growth. Differences in carbon sources are expected to influence and produce distinct yogurt characteristics. Therefore, this study aimed to investigate the effect of various carbon sources on the characteristics of purple sweet potato yogurt. The experiment was conducted using a Randomized Block Design (RBD) with a single treatment factor: the type of carbon source. Six treatments were tested, namely: no sugar (control), granulated sugar, palm sugar, sugarcane juice, coconut sugar, and honey. The results indicated that different carbon sources caused variations in total dissolved solids, total lactic acid bacteria, total titratable acidity, and total reducing sugars. Carbon sources significantly affected titratable acidity, reducing sugar content, total dissolved solids, color, taste, and the overall sensory evaluation of purple sweet potato yogurt. The yogurt produced exhibited titratable acidity values ranging from 1.69% to 1.86%, reducing sugar content from 1.11% to 1.46%, total LAB counts from 0.28 to 89.50 × 10¹0 CFU/g, and total dissolved solids from 10.25 to 17.75 °Brix. Sensory evaluation scores ranged as follows: color preference 2.83–4.26 (dislike to like), texture 3.43–3.76 (like), aroma 3.53–3.70 (like), taste 2.67–3.70 (dislike to like), and overall acceptability 3.43–3.90 (like).